Anti-ultraviolet polyester material and preparation method and application thereof

By adding modified bentonite to PET polyester material and using laser irradiation to form nano-scale microstructures, the problem of degradation of PET polyester material during long-term ultraviolet exposure is solved, significantly improving the UV resistance and thermal stability of the material and mechanical properties.

CN118638304BActive Publication Date: 2025-02-18JIANGSU YIERMAN NEW MATERIAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410756643.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-02-18
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

Conventional PET polyester materials are prone to degradation under long-term ultraviolet exposure, resulting in a decline in material performance, affecting its service life and application range, especially in outdoor environments, the performance requirements for anti-ultraviolet rays are more stringent.

Method used

By adding modified bentonite, nanoscale microstructure is formed by laser irradiation treatment, which increases the surface area and porosity of bentonite, thereby improving the UV resistance of PET polyester.

Benefits of technology

It significantly improves the UV resistance of PET polyester, enhances the thermal stability and mechanical properties of the material, extends the service life of the material, and has a wider and more reliable application in the field of photovoltaic modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004889642220000101
    Figure BDA0004889642220000101
Patent Text Reader

Abstract

The present invention relates to the technical field of new materials, and specifically proposes an anti-ultraviolet polyester material and a preparation method and application thereof, wherein the raw materials include terephthalic acid, ethylene glycol, and modified bentonite, wherein the modified bentonite is obtained by laser irradiation treatment of bentonite. The anti-ultraviolet polyester material of the present invention uses bentonite modified by laser irradiation to significantly improve the anti-ultraviolet performance of PET polyester, and the bentonite modification cost is low, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of new materials, and in particular to an anti-ultraviolet polyester material and a preparation method and application thereof. Background Art

[0002] Polyethylene terephthalate, or PET for short, is a widely used thermoplastic polymer. PET has many excellent physical and chemical properties, making it very popular in various fields. However, conventional PET materials are prone to degradation under long-term ultraviolet exposure, resulting in a decrease in material performance, affecting its service life and application range. Especially in outdoor environments, such as building materials, photovoltaic modules, automotive parts and other fields, the requirements for the material's anti-ultraviolet performance are more stringent.

[0003] At present, the methods for improving the UV resistance of PET polyester materials mainly include adding UV absorbers, light stabilizers or other surface treatment technologies. However, these methods have some limitations, such as the stability of additives, cost issues and the complexity of surface treatment. Providing a polyester material with better UV resistance has become one of the technical problems to be solved urgently. Summary of the invention

[0004] In view of this, the present invention proposes an anti-ultraviolet polyester material, aiming to achieve the purpose of improving the anti-ultraviolet property of the polyester material by adding modified components.

[0005] The technical solution of the present invention is implemented as follows: the present invention provides an anti-ultraviolet polyester material, the raw materials of which include terephthalic acid, ethylene glycol and modified bentonite, wherein the modified bentonite is bentonite obtained after being treated with laser irradiation.

[0006] In the above-mentioned embodiment of the present invention, abundant nanoscale microstructures can be formed on the surface of bentonite after laser irradiation treatment. These microstructures increase the surface area and porosity of bentonite, thereby significantly enhancing its ability to absorb and scatter ultraviolet light. These nanoscale microstructures can effectively capture and disperse ultraviolet light, reduce the penetration of ultraviolet light into the interior of the PET matrix, and thus improve the anti-ultraviolet performance of PET polyester.

[0007] Secondly, laser irradiation treatment can also cause changes in the chemical properties of the bentonite surface, generate more active sites, and improve surface energy. These modifications improve the interfacial compatibility between the bentonite and the PET matrix, allowing the bentonite to be more evenly dispersed in the PET matrix to form a more stable composite material structure. At the same time, the good dispersibility and stable interface effect formed above can increase the propagation path of ultraviolet rays inside the material, thereby significantly reducing the probability of ultraviolet rays passing through the material and further improving the material's resistance to ultraviolet rays.

[0008] Moreover, the bentonite modified by laser irradiation improves the durability of the material and enhances its anti-aging properties.

[0009] In some embodiments, the method for preparing modified bentonite includes: spreading the bentonite to be treated flat, and performing laser scanning on the spread bentonite.

[0010] In some embodiments, the parameters of the laser scanning process include: laser power of 5W-20W, pulse frequency of 10kHz-100kHz, pulse width of 50ns-200ns, and scanning speed of 100mm / s-1000mm / s.

[0011] In the above-mentioned embodiment, when the laser power is lower than 5W, insufficient power may be caused, and an effective micro-nano structure cannot be formed on the surface of bentonite; and when the laser power exceeds 20W, it is easier to cause ablation damage to bentonite, resulting in performance degradation, causing uneven modification, and ultimately affecting the anti-ultraviolet performance. The pulse frequency is preferably 10kHz-100kHz because, within this range, more efficient and dense microstructure processing can be achieved. If it is lower than this frequency, the processing efficiency is low, the surface modification is uneven, and the microstructure is not dense enough. If it is higher than this frequency, local heat accumulation may occur, causing structural damage to bentonite. Similarly, the above-mentioned pulse width is a relatively moderate range. Too short will result in too high energy density, and too long will result in insufficient energy of a single pulse. The screening of the scanning speed is also to avoid heat accumulation and insufficient energy.

[0012] In the above embodiment, preferably, when the bentonite is being spread, its thickness is preferably 50-500 μm. If the bentonite is too thin, the laser treatment of the bentonite may be damaged. If the bentonite is too thick, the laser treatment may fail to penetrate the entire thickness range, resulting in uneven modification.

[0013] In some embodiments, after the laser scanning treatment, the method further comprises immersing the bentonite in a UV absorber solution for 5-10 minutes, filtering and drying to obtain modified bentonite.

[0014] In some embodiments, the UV absorber is a benzophenone type ultraviolet absorber, and the solvent of the UV absorber solution is xylene.

[0015] In some embodiments, the UV absorber may specifically be selected from UV-P, UV-O, UV-9, UV-531, UV-327, and the like.

[0016] In some embodiments, the mass concentration of the UV absorber solution is 30-40%.

[0017] In the above embodiment, after the bentonite is treated with laser, it is immersed in a UV absorber to form a UV absorber layer on the surface of the bentonite. These UV absorbers can be enriched in the nanoscale microstructure to provide additional ultraviolet absorption function. Combined with the physical shielding effect of the bentonite, the anti-ultraviolet performance of PET polyester is significantly improved. The main principle is that the micro-nanostructure increases the contact between ultraviolet rays and UV absorbers during the reflection and scattering of ultraviolet rays, thereby converting ultraviolet rays into low-energy heat energy for dissipation, reducing the damage of ultraviolet rays to polymer chains, and this energy conversion helps to improve the thermal stability of the material and reduce thermal degradation caused by ultraviolet rays; and the UV absorber can form a waterproof layer and a mechanical reinforcement structure on the surface of the bentonite, while improving the moisture resistance and mechanical properties of PET polyester.

[0018] In some embodiments, the molar ratio of terephthalic acid:ethylene glycol is 1:(1.3-1.5).

[0019] In some embodiments, the modified bentonite is added in an amount of 1-5% by weight of terephthalic acid.

[0020] In a second aspect, the present invention also provides a method for preparing the above-mentioned UV-resistant polyester material, comprising: heating terephthalic acid, ethylene glycol and modified bentonite to 220-260°C under the action of a catalyst, while maintaining the pressure at 0-0.3MPa, and keeping the temperature for reaction for 2-6h, and then heating to 270-290°C, while maintaining the vacuum degree at 0-80Pa, and keeping the temperature for reaction for 2-4h to obtain the UV-resistant polyester material.

[0021] In some embodiments, the catalyst is antimony trioxide, and the amount of the catalyst is 0.02-0.05% by weight of the phthalic acid.

[0022] In a third aspect, the present invention further provides an application of the above-mentioned UV-resistant polyester material, specifically, application in photovoltaic modules, such as photovoltaic back panels.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention adopts laser modified bentonite to modify PET polyester, which significantly improves the shielding and absorption conversion capabilities of ultraviolet rays, improves the ultraviolet resistance of PET polyester, and the contact area between the laser modified bentonite and the PET polyester matrix is ​​larger, the heat transfer is faster, and the thermal stability of PET polyester is improved. Moreover, the addition of laser modified bentonite can significantly improve the mechanical properties of PET polyester. After further modification treatment with a surface UV absorber, the antioxidant performance and moisture-proof performance can be further improved, so that the application of PET polyester in the field of photovoltaic components is more extensive and reliable. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.

[0027] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.

[0028] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.

[0029] Example 1

[0030] Preparation of a UV-resistant polyester material:

[0031] Terephthalic acid, ethylene glycol, modified bentonite and antimony trioxide were mixed and stirred, heated to 220°C, and the pressure was 0.3MPa. The mixture was stirred and reacted for 6 hours. Then the vacuum degree of the system was adjusted to 80pa, the temperature was raised to 270°C, and the mixture was stirred and reacted for 2 hours to obtain PET polyester. The molar ratio of terephthalic acid to ethylene glycol was 1:1.3, the amount of modified bentonite added was 1% of the weight of terephthalic acid, and the amount of antimony trioxide added was 0.02% of the weight of terephthalic acid.

[0032] Preparation method of modified bentonite: spread the bentonite on the support plate of the laser equipment with a thickness of 100 μm, and then scan the spread bentonite with a laser. The scanning parameters are as follows: laser power is 10 W, pulse frequency is 50 kHz, pulse width is 100 ns, and scanning speed is 500 mm / s.

[0033] Example 2

[0034] Preparation of a UV-resistant polyester material:

[0035] Terephthalic acid, ethylene glycol, modified bentonite and antimony trioxide were mixed and stirred, heated to 240°C, and the pressure was 0.2MPa. The mixture was stirred and reacted for 4 hours. Then the vacuum degree of the system was adjusted to 60pa, the temperature was raised to 280°C, and the mixture was stirred and reacted for 3 hours to obtain PET polyester. The molar ratio of terephthalic acid to ethylene glycol was 1:1.4, the amount of modified bentonite added was 3% of the weight of terephthalic acid, and the amount of antimony trioxide added was 0.03% of the weight of terephthalic acid.

[0036] Preparation method of modified bentonite: spread the bentonite on the support plate of the laser equipment with a thickness of 100 μm, and then scan the spread bentonite with a laser. The scanning parameters are as follows: laser power is 10 W, pulse frequency is 50 kHz, pulse width is 100 ns, and scanning speed is 500 mm / s.

[0037] Example 3

[0038] Preparation of a UV-resistant polyester material:

[0039] Terephthalic acid, ethylene glycol, modified bentonite and antimony trioxide are mixed and stirred, heated to 260°C, and the pressure is normal pressure. The mixture is stirred and reacted for 2 hours. Then, the temperature is raised to 290°C under normal pressure, and the mixture is stirred and reacted for 2 hours to obtain PET polyester. The molar ratio of terephthalic acid to ethylene glycol is 1:1.5, the amount of modified bentonite added is 5% of the weight of terephthalic acid, and the amount of antimony trioxide added is 0.05% of the weight of terephthalic acid.

[0040] Preparation method of modified bentonite: spread the bentonite on the support plate of the laser equipment with a thickness of 100 μm, and then scan the spread bentonite with a laser. The scanning parameters are as follows: laser power is 10 W, pulse frequency is 50 kHz, pulse width is 100 ns, and scanning speed is 500 mm / s.

[0041] Example 4

[0042] Preparation of a UV-resistant polyester material:

[0043] Terephthalic acid, ethylene glycol, modified bentonite and antimony trioxide were mixed and stirred, heated to 240°C, and the pressure was 0.2MPa. The mixture was stirred and reacted for 4 hours. Then the vacuum degree of the system was adjusted to 60pa, the temperature was raised to 280°C, and the mixture was stirred and reacted for 3 hours to obtain PET polyester. The molar ratio of terephthalic acid to ethylene glycol was 1:1.4, the amount of modified bentonite added was 3% of the weight of terephthalic acid, and the amount of antimony trioxide added was 0.03% of the weight of terephthalic acid.

[0044] Preparation method of modified bentonite: spread the bentonite on the support plate of the laser equipment with a laying thickness of 100 μm, and then scan the spread bentonite with a laser. The scanning parameters are as follows: laser power is 5 W, pulse frequency is 100 kHz, pulse width is 50 ns, and scanning speed is 1000 mm / s.

[0045] Example 5

[0046] Preparation of a UV-resistant polyester material:

[0047] Terephthalic acid, ethylene glycol, modified bentonite and antimony trioxide were mixed and stirred, heated to 240°C, and the pressure was 0.2MPa. The mixture was stirred and reacted for 4 hours. Then the vacuum degree of the system was adjusted to 60pa, the temperature was raised to 280°C, and the mixture was stirred and reacted for 3 hours to obtain PET polyester. The molar ratio of terephthalic acid to ethylene glycol was 1:1.4, the amount of modified bentonite added was 3% of the weight of terephthalic acid, and the amount of antimony trioxide added was 0.03% of the weight of terephthalic acid.

[0048] Preparation method of modified bentonite: spread the bentonite on the support plate of the laser equipment with a laying thickness of 100 μm, and then scan the spread bentonite with a laser. The scanning parameters are as follows: laser power is 20 W, pulse frequency is 10 kHz, pulse width is 200 ns, and scanning speed is 100 mm / s.

[0049] Example 6

[0050] Preparation of a UV-resistant polyester material:

[0051] Terephthalic acid, ethylene glycol, modified bentonite and antimony trioxide were mixed and stirred, heated to 240°C, and the pressure was 0.2MPa. The mixture was stirred and reacted for 4 hours. Then the vacuum degree of the system was adjusted to 60pa, the temperature was raised to 280°C, and the mixture was stirred and reacted for 3 hours to obtain PET polyester. The molar ratio of terephthalic acid to ethylene glycol was 1:1.4, the amount of modified bentonite added was 3% of the weight of terephthalic acid, and the amount of antimony trioxide added was 0.03% of the weight of terephthalic acid.

[0052] Preparation method of modified bentonite: spread the bentonite on the support plate of the laser equipment with a thickness of 100 μm, and then scan the spread bentonite with a laser. The scanning parameters are as follows: laser power is 10W, pulse frequency is 50kHz, pulse width is 100ns, and scanning speed is 500mm / s. After scanning, the bentonite is immersed in a UV absorber solution for 5-10 minutes, filtered and dried to obtain modified bentonite. The UV absorber is UV-P, the solvent is xylene, and the mass concentration of the solution is 30%.

[0053] Example 7

[0054] Preparation of a UV-resistant polyester material:

[0055] Terephthalic acid, ethylene glycol, modified bentonite and antimony trioxide were mixed and stirred, heated to 240°C, and the pressure was 0.2MPa. The mixture was stirred and reacted for 4 hours. Then the vacuum degree of the system was adjusted to 60pa, the temperature was raised to 280°C, and the mixture was stirred and reacted for 3 hours to obtain PET polyester. The molar ratio of terephthalic acid to ethylene glycol was 1:1.4, the amount of modified bentonite added was 3% of the weight of terephthalic acid, and the amount of antimony trioxide added was 0.03% of the weight of terephthalic acid.

[0056] Preparation method of modified bentonite: spread the bentonite on the support plate of the laser equipment with a thickness of 100 μm, and then scan the spread bentonite with a laser. The scanning parameters are as follows: laser power is 10W, pulse frequency is 50kHz, pulse width is 100ns, and scanning speed is 500mm / s. After scanning, the bentonite is immersed in a UV absorber solution for 5-10 minutes, filtered and dried to obtain modified bentonite. The UV absorber is UV-P, the solvent is xylene, and the mass concentration of the solution is 40%.

[0057] Comparative Example 1

[0058] Preparation of a UV-resistant polyester material:

[0059] Terephthalic acid, ethylene glycol, bentonite and antimony trioxide were mixed and stirred, heated to 240°C, and the pressure was 0.2MPa. The mixture was stirred and reacted for 4 hours. Then the vacuum degree of the system was adjusted to 60pa, the temperature was raised to 280°C, and the mixture was stirred and reacted for 3 hours to obtain PET polyester. The molar ratio of terephthalic acid to ethylene glycol was 1:1.4, the amount of bentonite added was 3% of the weight of terephthalic acid, and the amount of antimony trioxide added was 0.03% of the weight of terephthalic acid.

[0060] Comparative Example 2

[0061] Preparation of a UV-resistant polyester material:

[0062] Terephthalic acid, ethylene glycol, modified bentonite and antimony trioxide were mixed and stirred, heated to 240°C, and the pressure was 0.2MPa. The mixture was stirred and reacted for 4 hours. Then the vacuum degree of the system was adjusted to 60pa, the temperature was raised to 280°C, and the mixture was stirred and reacted for 3 hours to obtain PET polyester. The molar ratio of terephthalic acid to ethylene glycol was 1:1.4, the amount of modified bentonite added was 3% of the weight of terephthalic acid, and the amount of antimony trioxide added was 0.03% of the weight of terephthalic acid.

[0063] Preparation method of modified bentonite: soak bentonite in UV absorber solution for 5-10 minutes, filter and dry to obtain modified bentonite. The UV absorber is UV-P, the solvent is xylene, and the mass concentration of the solution is 30%.

[0064] Comparative Example 3

[0065] Preparation of a polyester material:

[0066] Terephthalic acid, ethylene glycol and antimony trioxide were mixed and stirred, heated to 240°C, and the pressure was 0.2MPa. The mixture was stirred and reacted for 4 hours. Then the vacuum degree of the system was adjusted to 60pa, the temperature was raised to 280°C, and the mixture was stirred and reacted for 3 hours to obtain PET polyester. The molar ratio of terephthalic acid to ethylene glycol was 1:1.4, and the amount of antimony trioxide added accounted for 0.03% of the weight of terephthalic acid.

[0067] Performance Testing:

[0068] The polyester materials prepared in the examples and comparative examples were used for sheet casting, biaxial stretching, and film formation after shaping to prepare a PET polyester film with a thickness of 250 μm. The biaxial stretching ratio was 4 times, and the shaping temperature was 240° C. The prepared PET polyester film was tested for water vapor barrier properties and anti-ultraviolet properties, wherein:

[0069] The water vapor barrier test method refers to GB / T 21529-2008;

[0070] The UV resistance test method includes: using a UV-visible spectrophotometer to test the UV blocking rate of the film at 280-390nm and testing the UV aging performance of the polyester film in accordance with IEC61215:2005. The specific results are shown in the following table:

[0071]

[0072] It is not difficult to see from the above data that the modification of PET polyester with bentonite modified by laser irradiation can significantly improve the UV blocking rate, and has better anti-UV performance under long-term UV irradiation, especially after laser irradiation treatment and then UV absorber immersion treatment, which can further improve the anti-UV performance.

[0073] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An anti-ultraviolet polyester material, characterized in that: The raw materials of the anti-ultraviolet polyester material include terephthalic acid, ethylene glycol, and modified bentonite. The modified bentonite is obtained by laser irradiation treatment of bentonite. The preparation method of the modified bentonite includes: flattening the bentonite to be treated, and performing laser scanning treatment on the flattened bentonite. The parameters of the laser scanning treatment include: laser power of 10W, pulse frequency of 50kHz, pulse width of 100ns, and scanning speed of 500mm / s. After the laser scanning treatment, it also includes: immersing the bentonite in a UV absorber solution for 5-10min, filtering and drying to obtain the modified bentonite. The UV absorber is UV-P, the solvent of the UV absorber solution is xylene, and the mass concentration of the UV absorber solution is 30-40%.

2. The UV-resistant polyester material according to claim 1, characterized in that: The molar ratio of terephthalic acid:ethylene glycol is 1:(1.3-1.5).

3. The UV-resistant polyester material according to claim 1, characterized in that: The added amount of the modified bentonite accounts for 1-5% of the weight of terephthalic acid.

4. The method for preparing the UV-resistant polyester material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: heating terephthalic acid, ethylene glycol and modified bentonite to 220-260°C under the action of a catalyst, while maintaining the pressure at 0-0.3MPa, and carrying out a heat preservation reaction for 2-6h; then heating to 270-290°C, while maintaining the vacuum degree at 0-80Pa, and carrying out a heat preservation reaction for 2-4h to obtain an anti-ultraviolet polyester material.

5. Use of the UV-resistant polyester material according to any one of claims 1 to 3 in photovoltaic modules.

Citation Information

Patent Citations

  • High-barrier anti-ultraviolet polyester film and preparation method thereof

    CN116285241A